2020
DOI: 10.1108/ijpsm-05-2020-0131
|View full text |Cite
|
Sign up to set email alerts
|

SMEs' market orientation toward public sector customers in public procurement

Abstract: PurposeThis paper investigates how the market orientation of SMEs toward public sector customers enables firms to participate and succeed in public procurement.Design/methodology/approachThe authors used a survey-based methodology. First, the authors reconfigured an empirical construct of market orientation for private sector markets to measure the market orientation toward public sector customers. Then they conducted a survey of Finnish firms to test the construct and how it predicted firm performance in publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 55 publications
(113 reference statements)
0
27
0
1
Order By: Relevance
“…Following previous studies (e.g. Reijonen et al , 2016; Flynn and Davis, 2017; Saastamoinen et al , 2020), we use the number of bids submitted (BIDS) and the number of contracts (CONTRACTS) won as a consortium as the proxies for activity and success in public sector tenders.…”
Section: Methodology and Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Following previous studies (e.g. Reijonen et al , 2016; Flynn and Davis, 2017; Saastamoinen et al , 2020), we use the number of bids submitted (BIDS) and the number of contracts (CONTRACTS) won as a consortium as the proxies for activity and success in public sector tenders.…”
Section: Methodology and Datamentioning
confidence: 99%
“…Bartlett scores of the resulting extracted components were used as the variables of interest in regression analyses. Since our dependent variables are count variables, we follow Saastamoinen et al (2020) and use negative binomial regression to investigate how networks are correlated with submitted consortium bids and won consortium contracts [2]. We also carry out a robustness check, using ordinary least squares (OLS) regression.…”
Section: Methodology and Datamentioning
confidence: 99%
“…Then, they need to design and commit to a medium-term strategy with allocated resources, and carry out a systematic selection of markets (identifying priority countries/bodies) and prepare to implement the aforementioned strategy. Saastamoinen et al (2020) and Reijonen et al (2016) have already shown that the level of SME participation in public tenders is linked to how entrepreneurial their approach is, i.e. how actively they perform in the initial search and presentation phases of the process.…”
Section: Discussionmentioning
confidence: 99%
“…Tendering capabilities and small and medium enterprise involvement in public procurement SME involvement in public procurement is a widely studied topic. Existing research examines aspects that include a firm's strategic orientation, regulatory quality, training, competitiveness and market orientation in relation to SME involvement (Saastamoinen et al, 2020;Tammi et al, 2017;Reijonen et al, 2018). Empirical research examining the influence of tendering capabilities on SME involvement in public procurement is still scarce.…”
Section: Small and Medium Enterprise Governance Mechanisms And Tendering Capabilitiesmentioning
confidence: 99%